Combining Ability Analysis for Yield and Its Component Traits in Wheat (Titicum aestivum L.) under Timely Sown Irrigated Condition - Gupta, Vishal Kumar; Agarwal, A. P.; Minz, Madhuri Grace (International Journal of Bio-resource and Stress Management, 2017)
The present investigation entitled “Combining ability analysis for yield and its component traits in wheat (Triticum aestivum L.) under timely sown irrigated condition” was carried out during Rabi 2015-16 and 2016-17 at the All India Co-ordinated Wheat & Barley improvement project, B.T.C. College of Agriculture and Research Station, Bilaspur (C.G.). The experiment was conducted in Randomized Complete Block design involving ten lines, four testers and 40 F1s hybrids of wheat with two replications for study of character associated with yield and yield contributing traits for combining ability analysis. Analysis of variance revealed that variance due to the line×tester was significant for almost all the characters studied.MP 1202, Chhattisgarh genhu 03 and HW 2045 are good general combiner for number of grains per spike. LOK 1 had highest GCA effect for 1000 seed weight and GW 322 is best combiner for seed yield per plant. Negative SCA for days to 50% flowering and maturity was recorded by GW 322×GW 2013–507 and Chattisgarh genhu 03×GW 2013–507 respectively. MP 1202×PBW 585 is the best specific combiner for 1000 seed weight. More than 70% of crosses show positive SCA effect for seed yield per plant. Hence these findings of general combiners and specific combiners will be useful for next breeding programme for increasing the seed yield per plant, number of grains per spike and 1000 seed weight.